Examining the Reciprocal Technique in Enhancing Students Reading Comprehension: An Experimental Research - Sabiq, Agus Husein; Maryam, Siti (Ethical Lingua: Journal of Language Teaching and Literature, 2025)
This study is to assess the efficacy of the reciprocal technique in enhancing the reading abilities of senior high school students in Purbalingga Regency, Central Java. The study employed a quasi-experimental research design, comprising an experimental group instructed by the reciprocal technique and a control group instructed via lecturing methods. Data were gathered using pre-tests and post-tests comprising 50 multiple-choice questions on recount texts. An independent t-test by IBM SPSS Statistics 27 was chosen for data analysis to compare the performance between the experimental and control groups, aligning with the study’s objective of determining the significant effect of the reciprocal technique. The independent t-test analysis revealed a significant difference between the two groups (p = 0.008), demonstrating that the reciprocal strategy was more effective in improving students' reading comprehension. This method, including encompassing prediction, inquiry, clarification, and summarization tactics, promotes active engagement, critical analysis, and cooperation among students. The results indicate that the reciprocal technique can enhance students' reading abilities and foster the creation of more innovative and participatory English teaching strategies.